1992
DOI: 10.1021/np50080a002
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Investigation and Anti-Inflammatory Activity of Vitex negundo Seeds

Abstract: The CHCl3 extract of the defatted seeds of Vitex negundo exhibited anti-inflammatory activity and yielded four triterpenoids: 3 beta-acetoxyolean-12-en-27-oic acid [1], 2 alpha, 3 alpha-dihydroxyoleana-5,12-dien-28-oic acid [2], 2 beta,3 alpha-diacetoxyoleana-5,12-dien-28-oic acid [3], and 2 alpha,3 beta-diacetoxy-18-hydroxyoleana-5,12-dien-28-oic acid [5]. This is the first report of the isolation of compounds 2, 3, and 5 from a natural source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 5 publications
4
47
0
Order By: Relevance
“…The phytochemical present in the leaf extract such as Flavonoids [38][39][40] iridoids [41][42][43], terpenes [44,45], and steroids [46] are the major classes of compounds isolated from this plant. Terpenoids are poorly water-soluble and hence may not be among prime moieties involved in the bioreduction reaction.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…The phytochemical present in the leaf extract such as Flavonoids [38][39][40] iridoids [41][42][43], terpenes [44,45], and steroids [46] are the major classes of compounds isolated from this plant. Terpenoids are poorly water-soluble and hence may not be among prime moieties involved in the bioreduction reaction.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…It has significant productive effect on glycoprotein metabolism [9]. Experiments have demonstrated that different parts of the plant especially leaves, fruits, roots and seeds possess anti-inflammatory and anti-arthritic activity [10][11][12][13][14].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Many species have been studied in relation their chemistry, which is characterized by the presence of C-glucosyl fl avones, ecdysteroids, diterpenes and iridoids (Brito, 1992), as well as in relation to their biological activities. Antiinfl ammatory (Sidhartha et al, 1990;Chawla, et al, 1991), wound healing (Sidhartha et al, 1990) and antiandrogenic (Bhargava, 1989) activities, as well as inhibition of lymphocyte proliferation (You et al, 1998) and smooth muscle relaxant effect (Dayrit et al, 1987;Dayrit & Lagurin, 1994) are among those described in literature. V. agnus-castus is actually used in the treatment of pre-menstrual syndrome and menopausal complaints (Mills & Bone, 2000).…”
Section: Introductionmentioning
confidence: 96%